KAJIAN KESESUAIAN LAHAN BUDIDAYA TANAMAN OBAT DENGAN APLIKASI SISTEM INFORMASI GEOGRAFIS (SIG) DI KAWASAN SUKU SAMBORI KABUPATEN BIMA - idin, Juna; Utaya, Sugeng; Astina, I Komang; Handoyo, Budi (International Journal of Natural Science and Engineering, 2017)
This research can provide the answer that the potential of the local area is quite potential and needs to be utilized wisely for the welfare of the community. The purpose of this research is to know the potential of medicinal plant cultivation land and to obtain data base on the suitability of medicinal plant cultivation area with application of Geographical Information System (GIS) as a medicinal plant area in Sambore Tribe Area. In this research using survey method with MLA (Multidiciplinaire Landscape Assessment) approach is a method to determine